BIOEKOLOGI BULU BABI (Echinoidea) DI PERAIRAN PANTAI NEGERI HUTUMURI KOTA AMBON: Bioekologi Bulu Babi (Echinoidea) Di Perairan Pantai Negeri Hutumuri Kota Ambon - Fiqih Muharby; Laura Siahainenia; Yuliana Natan (Jurnal Perikanan Unram, 2024)
Hutumuri Country has beaches which can be said to be strategic water areas due to their proximity to residential areas. The potential resource of sea urchins makes people use sea urchins as food animals when the seasons change. There are several types of sea urchins that are used as food by local people. Such as being used as a berth for fishing boats, bameti and other coastal activities which can result in disruption of the presence of aquatic organisms, including sea urchins (Echinoidea). The results of research at the Hutumuri State Beach location show that the level of gonad maturity in the Tripneustes gratilla species during the east season consists of 2 levels of gonads, and is moniated by (TKG III) with a size range of 51 - 60 mm wide in diameter. Meanwhile, during the transition season I, individuals were obtained with (TKG V) in the range of diameter 56 - 72 mm. The Echinometra mathaei species shows a gonad maturity level during the east season of 3 gonad levels, and is dominated by (TKG IV) with a diameter of 26 - 35 mm. Meanwhile, in the transition season I it was monasted by (TKG V) with a size range of 35 - 45 mm wide diameter. In the eastern monsoon, the Diadema antillarum species found that gonad maturity occurred at stages (TKG I & II) with a size range of 95 - 105 mm in width. Meanwhile, during the first season, the Diadema antillarum species could not be found at the research location, which is thought to be due to the influence of the season.